A Phenomenological Inquiry Into the Art of the Holocaust. Issue 3 (3rd July 2021) - Hlavek, Elizabeth
Abstract: This article describes a phenomenological inquiry into the art and narratives of artists of the Holocaust. The author interviewed four Holocaust survivors and one child of a Holocaust survivor, each of whom provided a narrative account of their experiences of creating artwork in camps or ghettos during World War II. Phenomenological analysis revealed a psychological structure or essence of these artists' experience based on identity, autonomy, comfort, hope, affirmation of existence, and witnessing. These findings are relevant to contemporary art therapy practice as they demonstrate functions of art to cope with and counter political duress.